Advanced system demonstration for utilization of biomass as an energy source. Volume V. Electrical and instrumentation elementary diagrams and instrument indexes (Wheelabrator Cleanfuel Corp., Washington, DC (USA), 1980)
This volume contains detailed drawings and diagrams of electrical systems and instruments which will be included in a biomass cogeneration facility in Maine. (DMC)